Connection method of W / CuCrZr alloy
By using CNT-Cu co-deposition technology to form a Cu/CNT composite film in the connection of tungsten-based materials and CuCrZr alloys, the problem of insufficient thermal conductivity of the connector in the prior art is solved, and W/CuCrZr with high strength and high thermal conductivity is achieved Alloy connectors, suitable for fusion reactor operating conditions.
Patent Information
- Application Number
- CN202411300325.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The existing tungsten-based materials and CuCrZr alloy connection technology pays less attention to the thermal conductivity of the connector, which leads to insufficient performance of the connector under high temperature and high thermal shock conditions during the operation of the fusion reactor, and the introduced thermal interface has an adverse impact on thermal conductivity.
Carbon nanotubes (CNT) and dispersant are added to copper plating solution for ultrasonic dispersion. The Cu/CNT composite film is formed by co-deposition and annealing of CNT-Cu. Combined with high temperature heating connection, the high strength and high thermal conductivity of W/CuCrZr alloy are achieved. connect.
The high strength and high thermal conductivity of the connector are achieved, the shear strength is increased by 1.4-2 times, the thermal conductivity is increased by about 25%, and the interface connection is tight without significant thermal resistance, which is suitable for industrial applications.
Smart Images

Figure CN119194424A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dissimilar metal connection, and in particular to a W / CuCrZr alloy connection method. Background Art
[0002] During the operation of a nuclear fusion reactor, a high-density ion flow (~10 24 m -2 / s), high temperature (500~3200℃), thermal shock (10~20MW / m 2 ) and high flux neutrons (14MeV), the service conditions of materials directly surrounding high-temperature plasma are extremely harsh. Tungsten has a high melting point and still has excellent strength and thermal conductivity at high temperatures. It also has excellent properties such as low physical sputtering rate, no chemical reaction with hydrogen and extremely low hydrogen retention. It is the preferred plasma-facing material in current fusion reactors. The plasma-facing material needs to be connected to the heat sink material to quickly transfer the heat load on the surface of the plasma-facing material. The heat sink material must also withstand periodic high heat loads and high doses of neutron irradiation. CuCrZr alloy has been used as a heat sink material in the tokamak device of modern ITER. Tungsten plasma-facing material needs to be connected to CuCrZr alloy heat sink material.
[0003] At present, the connection technology for tungsten-based materials and CuCrZr alloys is mainly aimed at improving the mechanical properties of the connection parts, and there is a lack of research on the thermal conductivity of the connection parts. For example, the patent with the patent document number CN111347147A discloses a method for hot isostatic pressing of tungsten and CuCrZr alloy using a pure iron intermediate layer, and the maximum shear strength can reach 200MPa, but the introduction of the pure iron intermediate layer will cause the connection part to be magnetic, and will introduce a brittle phase at the interface, and the complex interface will also bring higher interface thermal resistance; the document with the patent document number CN112359391A discloses a method for connecting ODS-W and CuCrZr alloy using tungsten surface nano-activation technology, and the shear strength of the connection part can reach 201MPa, but this connection technology will cause A large specific surface area is generated at the joint, resulting in an increase in the interface thermal resistance of the connector, which has an adverse effect on the thermal conductivity of the connector. In addition, since there is little attention paid to the thermal conductivity of tungsten-based materials and CuCrZr alloy connectors, as a reference, patent document No. CN107740006A discloses a method for preparing a Cu / W composite material using a tungsten fiber layer and a Cu plate, and the thermal conductivity of the obtained composite material is 210W / (m·K), while the thermal conductivity of the material obtained by the preparation method of a tungsten-copper gradient composite material disclosed in patent document No. CN115178740A is also about 200W / (m·K).
[0004] In view of the high temperature, extremely high thermal shock and heat load during the operation of fusion reactors, improving the thermal conductivity of W and CuCrZr alloy connectors is extremely important for improving the performance and stable operation of connectors. Existing connection technologies for tungsten-based materials and CuCrZr alloys pay little attention to the thermal conductivity of connectors, and the thermal interface introduced during the connection process is also an important factor that has an adverse effect on the thermal conductivity of connectors. Summary of the invention
[0005] The object of the present invention is to overcome the shortcomings of the prior art and provide a W / CuCrZr alloy connection method. The connection method provided by the present invention can realize a W / CuCrZr alloy connection piece with both high connection strength and high thermal conductivity; the connection method provided by the present invention is simple and convenient, has high connection efficiency, low production cost, and is easy to realize industrial application.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a W / CuCrZr alloy connection method, comprising the following steps:
[0008] 1) adding carbon nanotubes (CNTs) and a dispersant into a copper plating solution, wherein the mass fraction of CNTs is 1 to 5 g / L, and then performing ultrasonic dispersion to obtain a copper plating solution in which CNTs are uniformly dispersed;
[0009] 2) performing CNT-Cu co-deposition on the W plate in the copper plating solution in which CNTs are uniformly dispersed, and then annealing at a temperature of 400 to 980° C. to obtain a W plate with a Cu / CNT composite film deposited on the surface;
[0010] 3) The W plate with the Cu / CNT composite film deposited on the surface and the CuCrZr alloy plate are arranged opposite to each other, and pressure is applied to the obtained composite plate to perform high-temperature heating connection. The applied pressure is 80-130 MPa and the temperature is 800-1050°C to obtain a W / CuCrZr alloy connector.
[0011] Preferably, the CNT is a hydroxylated multi-walled carbon nanotube with an outer diameter of 30-50 nm, an inner diameter of 5-12 nm, a length less than 10 μm, a hydroxyl content of 0.70-1.50 wt.%, and a purity greater than 95%.
[0012] Preferably, the dispersant used in step 1) is octadecyltrimethylammonium bromide (OTAB), and its mass fraction in the copper plating solution in which CNTs are uniformly dispersed is 0.1-1 g / L.
[0013] Preferably, the composition and content of the copper plating solution in step 1) are as follows: 25-35 g CuSO4·5H2O, 45-55 g (NH4)2SO4, 20-26 g citric acid, and 0.05-0.2 g C7H5O3NS (saccharin) per liter of copper plating solution.
[0014] Preferably, the total ultrasonic dispersion time in step 1) is 0.5 to 3 hours, and cooling is performed for 30 to 60 seconds after each 3 to 5 minutes of ultrasonic dispersion to prevent overheating of the copper plating solution.
[0015] Preferably, before the CNT-Cu co-deposition in step 2), the W plate is surface treated, and the surface treatment process includes grinding, polishing and ultrasonic cleaning.
[0016] Preferably, in step 2), the CNT-Cu co-deposition process is electroplated using a pulse power supply with a pulse width of 100 to 500 μs, a pulse period of 1 to 10 ms, an electroplating time of 3 to 10 min, and a current density of 1 to 5 A / dm 2 .
[0017] Preferably, in step 2), the annealing is performed in a hydrogen atmosphere for 1 to 4 hours.
[0018] Preferably, before the W plate with the Cu / CNT composite film deposited on the surface and the surface to be connected of the CuCrZr alloy plate are arranged opposite to each other in step 3), the CuCrZr alloy plate is surface treated, and the surface treatment process includes grinding, polishing and ultrasonic cleaning.
[0019] Preferably, the surface to be connected of the W plate having the Cu / CNT composite film on its surface is the Cu / CNT composite film surface on the surface treated side, and the surface to be connected of the CuCrZr alloy plate is the surface treated surface.
[0020] Preferably, the method of applying pressure to the composite plate is to fix the composite plate with a high temperature resistant stainless steel clamp, and apply pressure to the composite plate through the clamp bolts.
[0021] Preferably, the high temperature heating connection is carried out in a hydrogen atmosphere, and the insulation time is 1 to 4 hours.
[0022] The present invention provides a W / CuCrZr alloy connection method, wherein CNT and a dispersant are added to a copper plating solution, ultrasonically dispersed, and a copper plating solution uniformly dispersed with CNT is obtained; a W plate is subjected to CNT-Cu co-deposition in the copper plating solution uniformly dispersed with CNT, and then annealed to obtain a W plate with a Cu / CNT composite film deposited on the surface; the W plate with the Cu / CNT composite film deposited on the surface and the surface to be connected of a CuCrZr alloy plate are arranged relative to each other, pressure is applied to the obtained composite plate, and high-temperature heating connection is performed to obtain a W / CuCrZr alloy connector. The present invention utilizes CNT-Cu co-deposition, annealing, and diffusion connection of a W plate and a CuCrZr alloy plate to achieve high-strength and high-thermal-conductivity connection between a W plate and a CuCrZr alloy plate, and the thickness of the Cu / CNTs composite intermediate layer is only 0.4-1 μm, which is much smaller than that of a CuCrZr alloy plate, and will not affect the performance of the CuCrZr alloy plate itself. The W / CuCrZr alloy connector prepared by the connection method provided by the present invention introduces CNT enhanced connection at the interface, which is beneficial to improve the bonding strength and thermal conductivity of the connector. Among them, the connection strength can reach 201.8MPa, which is about 1.4-2 times the strength of the W / CuCrZr alloy direct connector. At the same time, the introduction of high thermal conductivity CNT can improve the thermal conductivity of the connector, and there is no problem of surface nano-activation to increase the specific surface area and increase thermal resistance. The obtained connector has a thermal conductivity of about 250W / (m·K), which is about 25% higher than the thermal conductivity of the W / CuCrZr alloy direct connector (about 200W / (m·K)), and is higher than the thermal conductivity of the tungsten and copper alloy composite material obtained by the existing production technology. The connection interface of the W and CuCrZr alloy obtained by the present invention is flat, tightly connected, no obvious dewetting of Cu occurs, and the introduction of CNT in the W / CuCrZr alloy connector does not bring unnecessary performance (such as magnetism). The connection method provided by the present invention is simple and convenient, has high connection efficiency, low production cost, and is easy to realize industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the clamp used, wherein 1 is a nut, 2 is a high temperature resistant stainless steel fixing plate, 3 is a partition plate whose main component is boron nitride, and 4 is a bolt;
[0024] Figure 2 This is a physical picture of the W / CuCrZr alloy connector prepared in Example 1;
[0025] Figure 3 This is a SEM image of the interface of the W / CuCrZr alloy connector prepared in Example 1;
[0026] Figure 4is a stress-strain curve diagram of the shear test of the W / CuCrZr alloy connector prepared in Example 1;
[0027] Figure 5 is a stress-strain curve diagram of the shear test of the W / CuCrZr alloy connector prepared in Example 2;
[0028] Figure 6 is a stress-strain curve diagram of the shear test of the W / CuCrZr alloy connector prepared in Example 3;
[0029] Figure 7 The thermal conductivity curve of the W / CuCrZr alloy connector prepared in Example 1 at different temperatures;
[0030] Figure 8 This is the interface TEM image of the W / CuCrZr alloy connector prepared in Example 1. DETAILED DESCRIPTION
[0031] The technical scheme of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] In the embodiment, the CNT selected is a hydroxylated multi-walled carbon nanotube with an outer diameter of 30-50 nm, an inner diameter of 5-12 nm, a length less than 10 μm, a hydroxyl content of 0.70-1.50 wt.%, and a purity greater than 95%.
[0033] Example 1
[0034] Step 1: Place 28g CuSO4·5H2O, 50g (NH4)2SO4, 21g citric acid, and 0.1g / L C7H5O3NS in a beaker, add deionized water to make the volume 1L, then add a clean stirring bar and place it on a magnetic stirrer and stir for 12h to obtain a copper plating solution;
[0035] 2 g of CNT and 0.5 g of OTAB were placed in a copper plating solution, and ultrasonic dispersion was performed for 1 h in an ultrasonic disperser with a rated power of 1200 W. After each 5 min of ultrasonic dispersion, cooling was performed for 30 s to obtain a copper plating solution in which CNT was uniformly dispersed.
[0036] Step 2: The W plate and the CuCrZr alloy plate with a size of 30 mm × 10 mm × 2 mm were polished with 100#, 150#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500#, and 2000# sandpaper in turn, so that one side of the W plate and the CuCrZr alloy plate was in a mirror state; then ultrasonically cleaned in acetone, isopropanol, and methanol for 15 minutes in turn, and after cleaning, they were blown dry with high-pressure nitrogen and dried in a vacuum drying oven at a temperature of 30°C for 12 hours;
[0037] The surface treated W plate was placed in the copper plating solution uniformly dispersed with CNT for pulse electrodeposition, with a pure copper plate of 30 mm × 30 mm × 2 mm as the anode and the surface treated W plate as the cathode. The surface treated surface of the W plate was set opposite to the copper plate at a distance of 3 cm. During the pulse electrodeposition process, the pulse width was 200 μs, the pulse period was 1 ms, and the current density was 1.7 A / dm 2 , the deposition time is 5 min, after which the W plate is taken out, rinsed with deionized water, and stored in a vacuum drying oven to prevent oxidation of the Cu / CNT composite film;
[0038] The W plate after CNT-Cu co-deposition was placed in a tubular annealing furnace and annealed in a high-purity H2 atmosphere at a temperature of 400°C for 3 hours to obtain a W plate with a Cu / CNT composite film on the surface;
[0039] Step 3: The Cu / CNT composite film surface of the W plate with the Cu / CNT composite film on the surface treated side is arranged opposite to the surface treated surface of the CuCrZr alloy plate, and Figure 1 The clamp shown is used to fix the relatively arranged W / CuCrZr composite plate between two layers of stainless steel fixing plates (2), and a partition (3) whose main component is boron nitride is inserted between the stainless steel fixing plate and the composite plate to prevent diffusion connection between the stainless steel fixing plate and the composite plate at high temperature. The fixed clamp is locked by bolts (4) and nuts (1) and pressure is applied to the composite plate, and the applied pressure is 106MPa. The W / CuCrZr composite plate fixed by the clamp is placed in a tubular annealing furnace and connected by high-temperature heating at 980°C for 3h in a high-purity H2 atmosphere to obtain a W / CuCrZr alloy connector. The actual picture of the obtained W / CuCrZr alloy connector is shown in FIG. Figure 2 shown.
[0040] Testing and Characterization:
[0041] The interface SEM of the W / CuCrZr alloy connector obtained in Example 1 is as follows: Figure 3 As shown. Figure 3It can be seen that the interface between W and CuCrZr alloy is tightly connected without obvious gaps and holes.
[0042] The stress-strain curve of the shear test of the W / CuCrZr alloy connector obtained in Example 1 is shown in FIG. Figure 4 As shown by Figure 4 It can be seen that the shear strength of the W / CuCrZr alloy connector is as high as 201.8MPa.
[0043] The thermal conductivity of the W / CuCrZr alloy connector obtained in Example 1 was tested at different temperatures, and a comparative sample directly connected without CNT-Cu co-deposition was prepared for thermal conductivity testing. The thermal conductivity curve with temperature is shown in FIG. Figure 7 As shown by Figure 7 It can be seen that the thermal conductivity of the W / CuCrZr alloy connector obtained by the method provided by the present invention is increased by about 250 W / (m·K), which is significantly improved by about 25% compared with the thermal conductivity of the W / CuCrZr alloy direct connector (about 200 W / (m·K)).
[0044] The interface TEM image of the W / CuCrZr alloy connector obtained in Example 1 is as follows: Figure 8 shown.
[0045] Example 2
[0046] Step 1: Place 25g CuSO4·5H2O, 45g (NH4)2SO4, 20g citric acid, and 0.05g / L C7H5O3NS in a beaker, add deionized water to make the volume 1L, then add a clean stirring bar and place it on a magnetic stirrer and stir for 12h to obtain a copper plating solution;
[0047] 1 g of CNT and 0.1 g of OTAB were placed in a copper plating solution, and ultrasonic dispersion was performed for 0.5 h in an ultrasonic disperser with a rated power of 1200 W. After each 4 min of ultrasonic dispersion, cooling was performed for 45 s to obtain a copper plating solution in which CNT was uniformly dispersed.
[0048] Step 2: The W plate and the CuCrZr alloy plate with a size of 30 mm × 10 mm × 2 mm were polished with 100#, 150#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500#, and 2000# sandpaper in turn, so that one side of the W plate and the CuCrZr alloy plate was in a mirror state; then ultrasonically cleaned in acetone, isopropanol, and methanol for 15 minutes in turn, and after cleaning, they were blown dry with high-pressure nitrogen and dried in a vacuum drying oven at a temperature of 30°C for 12 hours;
[0049] The surface treated W plate was placed in the copper plating solution uniformly dispersed with CNT for pulse electrodeposition, with a pure copper plate of size 30 mm × 30 mm × 2 mm as the anode and the surface treated W plate as the cathode. The surface treated surface of the W plate was set opposite to the copper plate at a distance of 3 cm. During the pulse electrodeposition process, the pulse width was 100 μs, the pulse period was 5 ms, and the current density was 1 A / dm 2 , the deposition time was 10 min, after which the W plate was taken out, rinsed with deionized water, and stored in a vacuum drying oven to prevent oxidation of the Cu / CNT composite film;
[0050] The W plate after CNT-Cu co-deposition was placed in a tubular annealing furnace and annealed in a high-purity H2 atmosphere at a temperature of 700°C for 1 h to obtain a W plate with a Cu / CNT composite film on the surface;
[0051] Step 3: The Cu / CNT composite film surface of the W plate with the Cu / CNT composite film on the surface treated side is arranged opposite to the surface treated surface of the CuCrZr alloy plate, by Figure 1 The W / CuCrZr composite plate was fixed with the clamp shown in the figure, and a pressure of 80 MPa was applied to the composite plate in the same manner as in Example 1. Then, the W / CuCrZr composite plate fixed with the clamp was placed in a tubular annealing furnace and subjected to high-temperature heating connection at 1050°C for 1 hour in a high-purity H2 atmosphere to obtain a W / CuCrZr alloy connector.
[0052] Testing and Characterization:
[0053] The stress-strain curve of the shear test of the W / CuCrZr alloy connector obtained in Example 2 is shown in FIG. Figure 5 As shown by Figure 5 It can be seen that the shear strength of the W / CuCrZr alloy connector is as high as 140MPa.
[0054] Example 3
[0055] Step 1: 35g CuSO4·5H2O, 55g (NH4)2SO4, 26g citric acid, and 0.2g C7H5O3NS were placed in a beaker, and deionized water was added to make the volume to 1L, and then a clean stirring bar was added and placed on a magnetic stirrer for stirring for 12h to obtain a copper plating solution;
[0056] 5 g of CNT and 1 g of OTAB were placed in a copper plating solution, and ultrasonic dispersion was performed for 3 h in an ultrasonic disperser with a rated power of 1200 W. After each 3 min of ultrasonic dispersion, cooling was performed for 60 s to obtain a copper plating solution in which CNT was uniformly dispersed.
[0057] Step 2: The W plate and the CuCrZr alloy plate with a size of 30 mm × 10 mm × 2 mm were polished with 100#, 150#, 240#, 400#, 600#, 800#, 1000#, 1200#, 1500#, and 2000# sandpaper in turn, so that one side of the W plate and the CuCrZr alloy plate was in a mirror state; then ultrasonically cleaned in acetone, isopropanol, and methanol for 15 minutes in turn, and after cleaning, they were blown dry with high-pressure nitrogen and dried in a vacuum drying oven at a temperature of 30°C for 12 hours;
[0058] The surface treated W plate was placed in the copper plating solution uniformly dispersed with CNT for pulse electrodeposition, with a pure copper plate of 30 mm × 30 mm × 2 mm as the anode and the surface treated W plate as the cathode. The surface treated surface of the W plate was set opposite to the copper plate at a distance of 3 cm. During the pulse electrodeposition process, the pulse width was 500 μs, the pulse period was 10 ms, and the current density was 5 A / dm 2 , the deposition time was 3 min, after which the W plate was taken out, rinsed with deionized water, and stored in a vacuum drying oven to prevent oxidation of the Cu / CNT composite film;
[0059] The W plate after CNT-Cu co-deposition was placed in a tubular annealing furnace and annealed in a high-purity H2 atmosphere at a temperature of 980°C for 4 hours to obtain a W plate with a Cu / CNT composite film on the surface;
[0060] Step 3: The Cu / CNT composite film surface of the W plate with the Cu / CNT composite film on the surface treated side is arranged opposite to the surface treated surface of the CuCrZr alloy plate, by Figure 1 The W / CuCrZr composite plate was fixed with the clamp shown in the figure, and a pressure of 130 MPa was applied to the composite plate in the same manner as in Example 1. Then, the W / CuCrZr composite plate fixed with the clamp was placed in a tubular annealing furnace and subjected to high-temperature heating connection at 800°C for 4 hours in a high-purity H2 atmosphere to obtain a W / CuCrZr alloy connector.
[0061] Testing and Characterization:
[0062] The stress-strain curve of the shear test of the W / CuCrZr alloy connector obtained in Example 3 is shown in FIG. Figure 6 As shown by Figure 6 It can be seen that the shear strength of the W / CuCrZr alloy connector is as high as 135Mpa.
[0063] The results of the embodiment show that by connecting W and CuCrZr alloy using the connection method provided by the present invention, the shear strength of the obtained connection piece can reach up to 201.8 MPa, and the thermal conductivity is about 250 W / (m·K), which is about 25% higher than that of the W / CuCrZr direct connection piece, and the interface connection is tight.
[0064] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.
Claims
1. A method for connecting W / CuCrZr alloy, characterized in that: The steps include: 1) adding carbon nanotubes (CNTs) and a dispersant into a copper plating solution, wherein the mass fraction of CNTs is 1 to 5 g / L, and then performing ultrasonic dispersion to obtain a copper plating solution in which CNTs are uniformly dispersed; 2) performing CNT-Cu co-deposition on the W plate in the copper plating solution in which CNTs are uniformly dispersed, and then annealing at a temperature of 400 to 980° C. to obtain a W plate with a Cu / CNT composite film deposited on the surface; 3) The W plate with the Cu / CNT composite film deposited on the surface and the CuCrZr alloy plate are arranged opposite to each other, and pressure is applied to the obtained composite plate to perform high-temperature heating connection. The applied pressure is 80-130 MPa and the temperature is 800-1050°C to obtain a W / CuCrZr alloy connector.
2. The W / CuCrZr alloy connection method according to claim 1, characterized in that: CNT is a hydroxylated multi-walled carbon nanotube with an outer diameter of 30-50 nm, an inner diameter of 5-12 nm, a length of less than 10 μm, a hydroxyl content of 0.70-1.50 wt.%, and a purity greater than 95%.
3. The W / CuCrZr alloy connection method according to claim 1, characterized in that: The dispersant used in step 1) is octadecyltrimethylammonium bromide (OTAB), and its mass fraction in the copper plating solution in which CNTs are uniformly dispersed is 0.1-1 g / L.
4. The W / CuCrZr alloy connection method according to claim 1, characterized in that: The composition and content of the copper plating solution are as follows: each liter of the copper plating solution contains 25-35g CuSO4·5H2O, 45-55g (NH4)2SO4, 20-26g citric acid, and 0.05-0.2g C7H5O3NS.
5. The W / CuCrZr alloy connection method according to claim 1, characterized in that: Step 1) The total ultrasonic dispersion time is 0.5 to 3 hours, and cooling is performed for 30 to 60 seconds after each 3 to 5 minutes of ultrasonication to prevent the copper plating solution from overheating.
6. The W / CuCrZr alloy connection method according to claim 1, characterized in that: Step 2) The CNT-Cu co-deposition process uses a pulse power supply for electroplating, with a pulse width of 100 to 500 μs, a pulse period of 1 to 10 ms, an electroplating time of 3 to 10 min, and a current density of 1 to 5 A / dm 2 .
7. The W / CuCrZr alloy connection method according to claim 1, characterized in that: In step 2), annealing is performed in a hydrogen atmosphere for 1 to 4 hours.
8. The W / CuCrZr alloy connection method according to claim 1, characterized in that: The method for applying pressure to the composite plate is to fix the composite plate with a high temperature resistant stainless steel clamp, and apply pressure to the composite plate through the clamp bolts.
9. The W / CuCrZr alloy connection method according to claim 1, characterized in that: Step 3) High temperature heating connection is carried out in a hydrogen atmosphere, and the insulation time is 1 to 4 hours.
Citation Information
Patent Citations
Cu / W composite material with anisotropic property and preparation method thereof
CN107740006A
Tungsten and heat sink material hot isostatic pressing connecting method
CN111347147A
Connecting method of ODS-W / CuCrZr alloy
CN112359391A
Tungsten copper functionally graded material and preparation method thereof
CN115178740A
Preparation method for CNT (Carbon Nanotube)-enhanced W-Cu thermal composite material
CN103849824A
